1991
DOI: 10.3109/01485019108987656
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Sperm Surface Sialic Acid Induces Phagocytosis: An Assay with a Monoclonal Antibody T21, Which Recognizes a 54K Sialoglycoprotein

Abstract: Using a monoclonal antibody T21, we reported that a mouse sperm maturation-associated antigen sialoglycoprotein of 54000 daltons (54K sialoglycoprotein) was secreted at the distal caput to proximal corpus epididymidis and that the 54K sialoglycoprotein had a hidden determinant (cryptodeterminant), which could be eliminated by sialidase treatment (Toshimori et al. (1988): Histochemistry 90: 195-200; (1990a): Biol Reprod 42:151-160; (1990b): Arch Histol Cytol 53:339-349). This study evaluated the mouse sperm su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…In addition, it has been established that O-acetylated sialic acids prevent the invasion of pathogens and influence the metabolic process of sialic acids [10,26]. On the other hand, the removal or loss of sialic acids from sperm surface is known to be necessary events for capacitation and zona pellucida recognition [15] and to induce phagocytosis of spermatozoa by macrophage [32]. In the wild boar, the existence of non-or O-acetylated sialic acids in the secretions of the disseminate prostate gland appears to play an important role for the stabilization of spermatozoa in terms of their metabolism, motility, and protection during ejaculation and ensuing transition to the female genital tract.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been established that O-acetylated sialic acids prevent the invasion of pathogens and influence the metabolic process of sialic acids [10,26]. On the other hand, the removal or loss of sialic acids from sperm surface is known to be necessary events for capacitation and zona pellucida recognition [15] and to induce phagocytosis of spermatozoa by macrophage [32]. In the wild boar, the existence of non-or O-acetylated sialic acids in the secretions of the disseminate prostate gland appears to play an important role for the stabilization of spermatozoa in terms of their metabolism, motility, and protection during ejaculation and ensuing transition to the female genital tract.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many sialylated and polysialylated glycoproteins are integrated into the plasma membrane of spermatozoa during epididymal transit (34,35). These glycoproteins inhibit, inter alia, in a sialic acid-dependent way the phagocytosis by leukocytes as seen in murine spermatozoa (30,36). In this regard, the substantial loss of sialic acid residues during epididymitis could prompt phagocytosis of spermatozoa during transit through the epididymis and/or the female reproductive tract, as already indicated (30,37).…”
Section: Discussionmentioning
confidence: 88%
“…Under normal conditions, neuraminidases are only activated in the female reproductive tract as a consequence of capacitation and/or acrosome reaction (8,10,12,29). Premature release of neuraminidases prior ejaculation is usually avoided, as untimely desialylation could result in elimination of spermatozoa by phagocytic cells (30). Under pathophysiological conditions such as bacterial epididymitis, considerable premature exocytosis of the acrosome has been observed in vivo and in vitro, which contributes substantially to the loss of fertilizing capacity, as shown by subsequent in vitro fertilization experiments in mice (5).…”
Section: Discussionmentioning
confidence: 99%
“…This will be true especially when antibodies are used for analyses of a membrane-bound sialoglycoprotein which is presumed to have a cryptodeterminant. The major antigen of MC81 is though to be identical to the 54K sialoglycoprotein which is specifically recognized by T21 (35,36,40) in terms of its cellular localization on mouse mature sperm flagellar surfaces from the corpus and cauda epididymidis, its proximal shift, its sialic acid-related masking and its molecular size and acidic nature. In addition, the epitope for the MC81 antibody is supposed to be present on sugar chains based on the observation that the epitope was sensitive to periodate treatment in a dose-dependent manner, as well as in the case of T21 (36).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported that monoclonal antibody T21 specifically recognizes a mouse sperm maturationassociated antigen of 54,000 dalton (54K) sialoglycoprotein; The 54K protein is considered to be secreted in the distal caput epididymidis, bound to the flagellar surface of sperm during transit in the epididymis, and involved in the protection of sperm from phagocytic cells (35)(36)(37)(38)40).…”
mentioning
confidence: 99%